Different danger signals differently impact on microglial proliferation through alterations of ATP release and extracellular metabolism. Issue 9 (4th April 2015) - George, Jimmy; Gonçalves, Francisco Q.; Cristóvão, Gonçalo; Rodrigues, Lisa; Meyer Fernandes, José Roberto; Gonçalves, Teresa; Cunha, Rodrigo A.; Gomes, Catarina A.
<x xml:space="preserve">Abstract</x> Microglia rely on their ability to proliferate in the brain parenchyma to sustain brain innate immunity and participate in the reaction to brain damage. We now studied the influence of different danger signals activating microglia, both internal (typified by glutamate, associated with brain damage) and external (using a bacterial lipopolysaccharide, LPS), on the proliferation of microglia cells. We found that LPS (100 ng/mL) increased, whereas glutamate (0.5 mM) decreased proliferation. Notably, LPS decreased whereas glutamate increased the extracellular levels of ATP. In contrast, LPS increased whereas glutamate decreased the extracellular catabolism of ATP into adenosine through ecto‐nucleotidases and ecto‐5'‐nucleotidase. Finally, apyrase (degrades extracellular ATP) abrogated glutamate‐induced inhibition of microglia proliferation; conversely, inhibitors of ecto‐nucleotidases (ARL67156 or α, β‐methylene ADP) and adenosine deaminase (degrades extracellular adenosine) abrogated the LPS‐induced increase of microglia proliferation, which was blocked by a selective A2A receptor antagonist, SCH58261 (50 nM). Overall, these results highlight the importance of the extracellular purinergic metabolism to format microglia proliferation and influence the spatio‐temporal profile of neuroinflammation in different conditions of brain damage. GLIA 2015;63:1636–1645